Các nhân tố ảnh hưởng đến tính kịp thời của báo cáo tài chính các công ty niêm yết trên Sở Giao dịch Chứng khoán Thành phố Hồ Chí Minh - Phạm Ngọc Toàn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
The timeliness is one of the major determinants contributing to the usefulness of a financial statement. This study aims to determine the factors impacting the timeliness of financial statements and point out the importance of the financial statements’ timeliness to investors, individuals, and the growth of financial markets. The data sample consists of 77 companies listed on Ho Chi Minh Stock Exchange (HOSE) over the period of 2010–2014. The analysis of regression is to examine the extent of the variables’ influence on the timeliness of financial statements. The findings of the study show that the determinants such as the type of financial statement, profitability, the type of auditing firms, and financial leverage have positive effects on the timeliness of financial statements. Contrary to this, firm size and business industry are negatively related to the timeliness of financial statements. The study would suggest some policy recommendations with the aim of enhancing the timeliness of firms’ financial statements on the stock exchange.
Keywords: Timeliness; Financial Statements; Firm Size; Industry; Financial Leverage; Profitability; Type of Auditing Firms